Peran Literasi Fintech dan Perilaku Budgeting terhadap Kesejahteraan Keuangan Mahasiswa - Dwi Lestari; Zuliyana Meti (Jurnal Kompetitif, 2026)
This study aims to analyze the influence of fintech literacy and budgeting behavior on the financial well-being of Accounting students of Tridinanti University. The study population was all 304 active students of the Accounting Study Program at Tridinanti University, graduating in the 2022–2025 intake. The research sample was determined using the Slovin formula with a 10% margin of error, resulting in 75 respondents. Data collection was conducted through questionnaires, while data analysis used multiple linear regression analysis with the help of SPSS version 25.0. Instrument testing included validity and reliability tests, as well as classical assumption tests consisting of normality, multicollinearity, and heteroscedasticity. The results showed that fintech literacy and budgeting behavior simultaneously had a positive and significant effect on student financial well-being, as indicated by a calculated F-value of 216.358 and a significance level of 0.000 (<0.05). Partially, fintech literacy has a positive and significant effect on financial well-being, as indicated by a t-value of 3.160 and a significance level of 0.002 (<0.05), as well as budgeting behavior which has a positive and significant effect on student financial well-being with a t-value of 10.946 and a significance level of 0.000 (<0.05). The coefficient of determination value shows that fintech literacy and budgeting behavior are able to explain 85.3% of the variation in student financial well-being, while 14.7% is influenced by other factors outside this study. It is recommended for future researchers to expand the study by adding income level variables. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh literasi fintech dan perilaku budgeting terhadap kesejahteraan keuangan mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tridinanti. Populasi penelitian adalah seluruh mahasiswa aktif FEB Universitas Tridinanti angkatan 2022–2025 yang berjumlah 304 mahasiswa. Sampel penelitian ditentukan menggunakan rumus Slovin dengan tingkat kesalahan 10%, sehingga diperoleh 75 responden. Teknik pengumpulan data dilakukan melalui penyebaran kuesioner, sedangkan analisis data menggunakan analisis regresi linier berganda dengan bantuan program SPSS versi 25.0. Pengujian instrumen meliputi uji validitas dan reliabilitas, serta uji asumsi klasik yang terdiri dari uji normalitas, multikolinearitas, dan heteroskedastisitas.Hasil penelitian menunjukkan bahwa secara simultan literasi fintech dan perilaku budgeting berpengaruh positif dan signifikan terhadap kesejahteraan keuangan mahasiswa, yang ditunjukkan dengan F hitung sebesar 216,358 dan tingkat signifikansi 0,000 (< 0,05). Secara parsial, literasi fintech berpengaruh positif dan signifikan terhadap kesejahteraan keuangan ditunjukkan dengan nilai t hitung sebesar 3,160 dan tingkat signifikansi 0,002 (< 0,05), begitu pula dengan perilaku budgeting yang memiliki pengaruh positif dan signifikan terhadap kesejahteraan keuangan mahasiswa dengan nilai t hitung sebesar 10,946 dan tingkat signifikansi 0,000 (< 0,05). Nilai koefisien determinasi menunjukkan bahwa literasi fintech dan perilaku budgeting mampu menjelaskan 85,3% variasi kesejahteraan keuangan mahasiswa, sementara 14,7% dipengaruhi oleh faktor lain di luar penelitian ini. Disarankan kepada peneliti selanjutnya untuk memperluas penelitian dengan menambahkan variabel tingkat pendapatan.